Population pharmacokinetics of ramipril in patients with chronic heart failure: A real-world longitudinal study - Trobec Katja Čvan; Grabnar Iztok; Trontelj Jurij; Lainščak Mitja; Kos Mojca Kerec (Acta Pharmaceutica)
In patients with chronic heart failure (CHF), the use of angiotensin-converting enzyme inhibitors, including ramipril, is recommended to reduce the risk of heart failure worsening, hospitalisation, and death. Our aim was to investigate the influence of body composition on the pharmacokinetics of ramipril and its active metabolite ramiprilat and to evaluate the changes in pharmacokinetics after prolonged therapy. Twenty-three patients with CHF who were on regular therapy with ramipril participated at the first study visit ( median age 77 years, 65 % male, and 70 % New York Heart Association Class II); 19 patients attended the second study visit and the median time between the two visits was 8 months. Pharmacokinetics were assessed using a nonlinear mixed-effects parent-metabolite model comprising two compartments for ramipril and one compartment for ramiprilat. The influence of body size and composition was best described by an allometric relationship with fat-free mass. In addition, ramipril clearance was related to patient age and daily ramipril dose, while clearance of ramiprilat was influenced by glome rular filtration rate and daily ramipril dose. There were no clinically relevant changes in the pharmacokinetics of ramipril and ramiprilat between the study visits. Due to the relatively stable pharmacokinetics of ramipril, regular outpatient visits at 6-month intervals seem appropriate to evaluate ramipril therapy.